How Firms' Quality Experts Shape Canadian Public Accountability Board Inspections and Their Outcomes: An Analysis of Intraprofessional Conflicts, Third‐Party Influences, and Relational Strategies† - Couchoux, Oriane; Malsch, Bertrand (Contemporary Accounting Research, 2022)
ABSTRACT In this study, we examine auditors' claims of professional disempowerment and strategic responses to Canadian Public Accountability Board (CPAB) inspections. Our research is based primarily on 27 semistructured interviews with audit partners (23) and managers (4) of large accounting firms. Drawing on key insights from institutional theory, we show that the tensions between inspectors and auditors reflect an intraprofessional tug‐of‐war between two competing but legitimate logics of professionalism. More specifically, our findings indicate that CPAB inspections have given rise to a mechanical logic of audit professionalism that is driven by the efforts of inspectors to promote a generalizable theoretical ideal of auditing that revolves around best practices and attention to technical minutiae. This mechanical logic competes with a clinical logic of audit professionalism that is driven by the efforts of audit partners and managers to promote a more relativistic, applied form of expert knowledge. To manage this dynamic of intra‐institutional complexity, quality experts (QEs) have emerged in firms' organizational structures as ambidextrous third parties—that is, professionals who master both logics and are capable of bridging the institutional divide by influencing the relationships between inspectors and auditors through a variety of brokering strategies. By considering inspectors as insiders rather than outsiders to the profession, we argue that auditors' claims of professional disempowerment should be interpreted carefully and critically. We also suggest that the professional autonomy and judgment of engagement partners and managers has been displaced significantly within firm boundaries into the hands of QEs. Our analysis offers a richer conceptualization of institutional ambidexterity by examining it as a relational process of social influence rather than as a set of individual characteristics.